The Effect of Financial Performance, Leverage and Company Size on Company Value in the Food and Beverage Manufacturing Sector - Noviyati; Wulandari Agustiningsih (International Journal of Asian Business and Management, 2023)
This study's objective is to empirically establish whether financial performance, leverage, and firm size have a partial or simultaneous impact on firm value for the Food and Beverage Manufacturing companies listed on the Indonesia Stock Exchange between 2018 and 2020. Financial success as determined by ROA, leverage as determined by DER, and company size as determined by Size—as well as one dependent variable—firm value as measured by PBV—make up this study. There are 23 companies in this study that fit the requirements and have a combined revenue of 69 financial statements in Between 2018 and 2020, businesses in the food and beverage industry listed on the Indonesia Stock Exchange (IDX). According to the research, a firm's financial performance increases its value. In light of the fact that the Leverage variable has an impact on company value, firm size positively affects the worth of the company. Based on the study's findings, it can be said that financial performance, leverage, and firm size all affect corporate value simultaneously food and beverage sector in 2018-2020